STUDY OF REOLOGICAL PROPERTIES OF NIMODIPIN SUPPOSITORIES - V. V. Gladyshev; V. V. Nagorny; N. N. Malecky; L. N. Vaniosova (Кубанский научный медицинский вестник, 2014)
Reological properties of nimodipin suppositories on poly (ethylene oxide) basis with 2% distillide monoglyceride depending on temperature conditions of suppository masses were studied. Temperature 50-55° C for technological operations of homogenization and pouring out suppository provided with necessary fluidity of suppository mass, even distribution of active substances and excipients and it was determined as optimal.